First demonstration on direct laser fabrication of lunar regolith parts - Krishna Balla, Vamsi; Roberson, Luke B.; O'Connor, Gregory W.; Trigwell, Steven; Bose, Susmita; Bandyopadhyay, Amit (Rapid prototyping journal, 2012)
Purpose - The purpose of this paper is to evaluate the feasibility of direct fabrication of lunar Martian regolith simulant parts, in a freeform environment, using Laser Engineering Net Shaping (LENS™) - an additive manufacturing technology.Design methodology approach - Bulk lunar regolith simulant structures were fabricated using a LENS™-750. Dense parts without any macroscopic defects were produced at a laser power of 50W, a scan speed of 20 mm s, and a powder feed rate of 12.36 g min. The laser processed parts were characterized using X-ray diffraction, differential scanning calorimetry, scanning electron microscope and X-ray photoelectron spectroscopy to evaluate the influence of laser processing on the microstructure, constituent phases and chemistry of lunar regolith simulant.Findings - A combination of laser parameters resulting in a 2.12 J mm2 laser energy appeared to be ideal for generating a melt pool necessary for lunar regolith powder deposition without excessive liquid pool spreading and cracking of solidified parts. The results show that LENS™ based laser processing transformed crystalline regolith into nanocrystalline and or amorphous regolith structures as a result of complete melting followed by resolidification. Laser processing also resulted in marginal changes in the composition of the regolith.Originality value - Establishment of a lunar Martian outpost necessitates the development of methods to utilize in situ mineral resources for various construction and resource extraction applications. Fabrication technologies are critical for habitat structure development, as well as repair and replacement of tools and parts at the outpost. Current experimental results presented in the paper clearly demonstrate that net shape regolith simulant parts can be fabricated using LENS™ by exploiting its capabilities.